Resistência ao cisalhamento de solo com raízes – ensaios de cisalhamento direto in situ - Maffra, Charles Rodrigo Belmonte (2018)
The increasing use of Soil Bioengineering in infrastructure works has required the improvement of the technical information regarding the behavior and performance of the plants which are used as building material. On this subject, the inclusion of plants on the calculation of geotechnical slope stability has been emphasized in recent years. To make this possible, the first step is to determine, in a representative way, the effect of plants on the shear strength of the soil, which is still a challenge due to the lack of specific equipment and standard procedures for conducting field tests with plants under natural or planting conditions. In order to contribute to these questions, this study aimed to investigate the effect of the woody species Phyllanthus sellowianus (Klotzsch) Müll. (Phyllanthaceae) on the soil resistance to in-situ direct shear and its influence on slope stability. To achieve this objective, the study was developed in two interdependent parts: 1) Analysis of the relationship between the plant aerial compartments and the root system resistance to the pullout; and 2) In-situ direct shear tests performed on soil with and without roots. The pullout and the in-situ direct shear experiments were performed in the Vale Vêneto district, in the municipality of São João do Polêsine, RS. In both experiments, the P. sellowianus planting was carried out using live cuttings collected from different plants. In the mowing and weeding area, the live cuttings were planted by direct planting system, in spacings of 1.0x1.0 m (pullout tests) and 0.7x0.7 m (shear tests). For the conduction of the pullout and the in-situ shear tests, devices specifically designed and developed for the tasks were used. In the study of the interdependence between the development of plant aerial compartments and the root system resistance, it was identified that the sum of the cross-sectional area of shoots (mm2) was the variable with the greatest capacity to describe the variations in the resistance of the roots of the plants. This variable, therefore, was used to representatively sample the plants to be used in in-situ direct shear tests. In the shear tests, it was identified that, after 12 months of field development, the plants did not influence the angle of internal friction of the soil, but they had influence on the soil cohesion, which provided an increase of up to 83.1%. Therefore, the plants acted as soil reinforcement elements. Regarding the influence of the plants on the slope stability, a positive contribution was verified since the plants influenced significantly the cohesion of the soil. The in-situ direct shear machine, developed to make feasible the present study, as well as the procedures that supported its use, were effective in the task of quantifying the effect of plants in the shear strength of the soil. Following the means and procedures used in the present study, the general aspect of the in-situ direct shear tests may evolve towards the elaboration of a standardized technical specification, which may be useful for slope geotechnical stabilization projects.